Understanding the impact of economic migrants and landless farmers on mass-produced housing and community space in China, using the case of Zhangjing, Suzhou. Issue 1 (2nd January 2018) - Choi, Hee Sun (Sunny); Reeve, Alan
ABSTRACT: As a consequence of the rapid, government-led and globally fuelled urban development that is occurring within China, an unplanned form of urbanization is emerging, whereby landless farmers and economic migrants are resettling and occupying both public space and housing in ways that deviate from the community development plan. The paper will use both historical and contemporary urban theory, together with a case study of Zhangjiing in Suzhou Industrial Park, China as means of critiquing and learning from these consequences and the planning and policy instruments in place. The case of Zhangjing can be critically reviewed in the context of Christopher Alexander's argument that when a new urban development is created which is modelled or predicated on a tree structure to replace the semi-lattice that was there before, the city takes a step towards dissociating itself from its geographical and cultural context.